2013 IEEE Conference on Computer Vision and Pattern Recognition 2013
DOI: 10.1109/cvpr.2013.39
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Bilateral Symmetry Plane Estimation in the Phase Domain

Abstract: We show that bilateral symmetry plane estimation for three-dimensional (3-D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Also, Bermanis et al [BAK10] proposed to evaluate the symmetry by comparing volumes through an angular difference function which can be efficiently computed using the 3D Pseudo‐polar Fourier Transform. Analogously, Kakarala et al [KKP13] described an optimization method that detects symmetry planes which can be interpreted as a linear phase in the spherical harmonic domain. More recently, Korman et al [KLAB14] proved an upper bound on the sampling density of the transformation group which guarantees to find symmetries with high probability.…”
Section: Related Workmentioning
confidence: 99%
“…Also, Bermanis et al [BAK10] proposed to evaluate the symmetry by comparing volumes through an angular difference function which can be efficiently computed using the 3D Pseudo‐polar Fourier Transform. Analogously, Kakarala et al [KKP13] described an optimization method that detects symmetry planes which can be interpreted as a linear phase in the spherical harmonic domain. More recently, Korman et al [KLAB14] proved an upper bound on the sampling density of the transformation group which guarantees to find symmetries with high probability.…”
Section: Related Workmentioning
confidence: 99%
“…Some of the material in this thesis has appeared elsewhere, including [77], [76], [78], [79] and [43].…”
Section: Outline and Contributionmentioning
confidence: 99%
“…The use of spherical harmonics allows us to specify the granularity of the shape while identifying the object's symmetry plane. It was recently shown in [43] that bilateral symmetry plane estimation may be carried out accurately, and efficiently, in the spherical harmonic domain. It was shown that the presence of bilateral symmetry in the 3-D shape is equivalent to a linear phase structure in the corresponding spherical harmonic coefficients.…”
Section: Extensions To 3-d Objectsmentioning
confidence: 99%
“…Furthermore, an automated framework to enable the parameter selection for various stochastic search procedures are discussed here. An extension of the stochastic search methods to the manifold §n [18] is also discussed along with an application to the problem of bilateral symmetry plane estimation for a 3D surface.…”
Section: Organization Of the Thesismentioning
confidence: 99%
“…Furthermore, the coefficients can be used to identify bilateral plane of symmetry [18]. This is achieved by formulating an optimization problem in the manifold § 3 , which is an isomorphic cover for the group S0(3) that parametrize rotations and reflections in 3 dimensions.…”
Section: Stochastic Search On a Manifoldmentioning
confidence: 99%